Essay on the nature & significance of economic science - Robbins, Lionel (London, 1948)
THE purpose of this essay is twofold. In the first place, it seeks to arrive at precise notions concerning the subject-matter of Economic Science and the nature of the generalisations of which Economic Science consists. Secondly it attempts to explain the limitations and the significance of these generalisations, both as a guide to the interpretation of reality and as a basis for political practice. At the present day, as a result of the theoretical developments of the last sixty years, there is no longer any ground for serious differences of opinion on these matters, once the issues are clearly stated. Yet, for lack of such statement, confusion still persists in many quarters, and false ideas are prevalent with regard to the pre occupations of the economist and the nature and the extent of his competence. As a result, the reputation of Economics suffers, and full advantage is not taken of the knowledge it confers. This essay is an attempt to remedy this deficiency-to make clear what it is that economists discuss and what may legitimately be expected as a result of their discussions. Thus on the one hand it may be regarded as a commentary on the methods and assumptions of pure theory: on the other hand, as a series of prolegomena to work in Applied Economics.
Keywords: Economics history